(untitled) (Ágora Journal, 2025)
Oswald de Andrade (1890-1954) published his Manifesto da Poesia Pau-Brasil in 1924, and his eponymous book of poetry the in following year, in the wake of what Mário de Andrade defined as the greatest intellectual orgy that artistic history had recorded up to that time — moment in which Paubrasilism was considered to be the starting point of the second phase of the modernist movement: the elaboration of a national culture. After a remarkable number of readers in the 1920s, his work gained new prominence ten years after his death due to its reinterpretation, brought around by tropicalist artists in the 1960s. Another important landmark was the XXIV Bienal de São Paulo (1998), with the central theme being the author’s anthropophagic ideas, which points to his referential consecration for Brazilian art, as well as his thematic relevance to scientific investigation as a whole. The purpose of this text is to investigate more recent productions of Oswald’s work, especially the one entitled Pau Brasil (which came to light on the occasion of his centenary), and to understand views and questions this work raises in the contemporary world through History — this while taking into account the validity of a historical speech that aims to the legitimization of São Paulo’s Modernism, with Oswald being one of this movement’s main exponents.